European Tourism Clusters: Directions for Restoring the Competitiveness of Ukrainian Tourism (Economics and region, 2023)
The article examines the state of tourism development in Ukraine during the war. It considers the experience of countries that survived the war. It is determined that the purpose of such trips is to support the country's residents and pilgrimages. The consequences of the military conflict are a change in the tourist heritage and an increase in demand for black and military tourism products. The clustering of the countries of the European region was carried out using the TTCI indicators for 2007-2019 in order to identify a potential cluster for Ukraine. The results of the cluster analysis showed the existence of five tourism clusters. A potential European tourism cluster, of which Ukraine could be a member, has been identified. The formation of European virtual-territorial tourism clusters is proposed. This approach will allow developing competitive tourist offers covering the maximum segment of consumers in the world.
Keywords: competitive; tourist cluster of the virtual territory; tourism development